MOTIVATING ENGLISH FOR SPECIFIC PURPOSES (ESP) STUDENTS - Mirzokulova, Xursanoy Ne’matjonovna (GOLDEN BRAIN, 2024)
ESP stands for "English for Specific Purposes" and refers to the teaching and learning of English for a specific purpose or field, such as business, medicine, or engineering.